If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -1(2x + 2) = x + -1(3x + -5) Reorder the terms: 3 + -1(2 + 2x) = x + -1(3x + -5) 3 + (2 * -1 + 2x * -1) = x + -1(3x + -5) 3 + (-2 + -2x) = x + -1(3x + -5) Combine like terms: 3 + -2 = 1 1 + -2x = x + -1(3x + -5) Reorder the terms: 1 + -2x = x + -1(-5 + 3x) 1 + -2x = x + (-5 * -1 + 3x * -1) 1 + -2x = x + (5 + -3x) Reorder the terms: 1 + -2x = 5 + x + -3x Combine like terms: x + -3x = -2x 1 + -2x = 5 + -2x Add '2x' to each side of the equation. 1 + -2x + 2x = 5 + -2x + 2x Combine like terms: -2x + 2x = 0 1 + 0 = 5 + -2x + 2x 1 = 5 + -2x + 2x Combine like terms: -2x + 2x = 0 1 = 5 + 0 1 = 5 Solving 1 = 5 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 4+7(x-8)=9-3(x-4) | | 1-4y=1 | | -14=-4+5x+3x | | 33m-14+14=33 | | x-7=34-7(x+7) | | 4x-1=113 | | 124-v=185 | | -7+3y=-16 | | 16+8y=80 | | 4v-4=-24 | | 2(x-4)-3=7-4x | | 3=(-6)+x | | -5p=0 | | -x-10y=-24 | | 56=2(15)+2w | | -2y+30=5y-5 | | 3x+5x+-4=-14 | | 5+2*[3(x+5)-(3x+11)]=11-4x | | 3x+3x+4x+2x= | | 2-4d=0 | | 3y-5t+10=36 | | -5/9y25 | | y=1E+06X+17211 | | 10u-3u=42 | | (X-2)2+(y+5)2=12 | | 69x+13=151 | | -30=5+5y | | 5x*y=2720 | | p/3=2p/3=1/4 | | 7x+20y=18 | | 28=m/7=43 | | Fx=4x^2+4x-15 |